(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Assessing the change in knowledge of mothers about caring for children under 5 years old with pneumonia at the Pediatric Department, National Lung Hospital in 2022 after health education intervention. Method: A health education intervention study with comparison before and after on 60 mothers with children under 5 years old with pneumonia treated at the Pediatric Department, National Lung Hospital from January to April. 2022. Results: Before the intervention, the percentage of mothers with correct knowledge about pneumonia was 58.1%. After health education, the percentage of mothers with correct knowledge about pneumonia was 100%. The difference was statistically significant with p<0.05. Conclusion: Mothers’ knowledge about disease, care and prevention of pneumonia is still limited before health education interventions. After health education, mothers’ knowledge improved significantly, which shows the effectiveness of health education in improving mothers’ knowledge about diseases, care and prevention of pneumonia.